(3GdCHjGJ GdCehjI GdYGeQI HGdCdZGR GdTgjI GdaGNQIs - (3YHO Gdedc Hf YHO GdSdGe Hf YHO GdMajX GHf OYSjf GdCehj GdbQTj,J (B1006 (3g` s
(3ChdgG (B:s
(3CeG HYO(B: (3agPg CdZGR LdJ YQGFS CHcGQ eNOQGJgG aj Mdd GdeYGfj Ydi efUI GdCdaGX hbO QJHJgG Ydi MQha GdeYLe s
(3BNQgG (B:s
(3hEf MPaJ GdQHY ef eWQOg aUMa GdHGbj Hcf eY GdpeYG JeJ GdCdZGR HMeO Gddg JYGdi hMSf Jhajbg s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B159 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B183s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B3 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs